Memorandum on the Fourth Five Year Plan - Planning Commission (Planning Commission, 1964)
This Memorandum sets out as a basis for further work, the tentative framework of the Fourth Five Year Plan. 2. Studies leading to the preparation of the Fourth Plan commenced about two years ago and have been pursued intensively since the mid-term Appraisal of the Third Plan. The Memorandum brings together briefly the more important results of these studies.It indicates the objectives and pattern of development, the broad relationships between different sectors and the choices which have to be made in determining policy and action for the future. 3. After consideration by the National Development Council, more detailed planning and preparation of projects will be undertaken by the Central Ministries and the State Governments and in relation to programmes of development in the private sector.
Government of India Planning Commission